Diagnosis of Vaso-Invasive Hepatocellular Carcinoma Involving the Medial Hepatic Vein and Right Portal Vein in a man presenting with Upper Gastrointestinal Bleeding and Melena - Furqan Ul Haq, Muhammad Ali, Sani Ul Hassan, Daneet Kumar, Yasir Ali, Farooque Islam, Tanveer Hamid, Syed Sadam Hussain, Waqar Ali Shah, Aman Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatocellular carcinoma (HCC) is one of the most fatal malignant tumors of the gastrointestinal tract in men as compared to women. It develops in the setting of chronic inflammation and cirrhosis. Major risk factors are hepatitis B and hepatitis C, alcoholic cirrhosis, and non-alcoholic fatty liver disease. It metastasizes to lungs, bones, portal vein and regional lymph nodes. Melena and hematemesis are the common presentations. Methodology: Case report study done in Swat Medical College, Rahman Medical Institution laboratory and Swat Medical Complex. Case: We have a confirmed case of HCC initially presenting with coffee color emesis and the previous 06 episodes from August to September 2022 with melena. Computed tomography (CT) abdomen with contrast showed a mass of irregular margins with vascular invasion. Histopathology showed HCC. The rationale of this case report is that we report a HCC case with vascular invasion. This patient is a candidate for systemic therapy, which would be guided by the assessment of financial factors, performance status and other comorbidities. Practical Implications: This study is going to prove the importance of finding out why the prognosis of HCCa becomes poor when vascular invasion such as hepatic veins, vena cava, portal veins or hepatic artery is present, in this study the invasion was in medial hepatic vein extending to right portal vein, that’s why his prognosis is considered to be poor as the disease has vascular invasion, if vessel were not invaded than there was a possible of local chemo and radiotherapy to target the tumor site and patient could have survived normal life. Results and conclusion: HCC is amongst the most lethal carcinomas with various causes, including hepatitis B and C virus infection, alcohol consumption, non-alcoholic fatty liver disease, etc. The risk of HCC recurrence increases many fold in macrovascular invasion as compared to microvascular invasion even after orthotopic liver transplant. Patients diagnosed with HCC should be thoroughly investigated for vascular invasion as it is one of the major factors in making decisions regarding treatment options. Keywords: Hepatocellular carcinoma, Vaso Invasion, Alpha-Fetoprotein, Cirrhosis, hepatitis B and C, liver masses,